Doorways to other worlds : towards successful Pacific s/p/aces in education : a thesis presented in partial fulfilment of the requirements for the Master of Education at Massey University - Smith, Talei (Massey University, 2011)
This thesis is an autoethnographic exploration of the processes by which my hybrid cultural identity has been constituted. The purpose of this thesis is to contribute to understandings of how better to facilitate the educational success of Pacific learners in a New Zealand context. Within the methodology of autoethnography, I follow the idea of the role of the researcher as a bricoleur to guide my explorations of the processes of my hybrid cultural identity construction. I use a combination of influences including Kerouac’s verse form of American Haiku as well as written and photographic mindmaps, to reflect on my embodied experiences. I have represented, through vignettes and poetry, the ways in which sensuous perspectives of scent, touch, hair, music and dance have created hybrid cultural understandings of place and space in my life. The discussions of my sensuous experiences are then explored through Bourdieu’s concepts of cultural capital and habitus. These concepts form the broad theoretical framework through which the educational implications of my hybrid cultural experiences are drawn out, in reference to an overriding ethic of empathy and care.
Keywords: Pacific Islanders; Education; Ethnic identity; Social life and customs; Autoethnography; Mindmaps; Hybrid cultural experiences; New Zealand